Banks of the Future: Putting a Puzzle Together Creatively - Thuiner, Sohella (Springer, 2016)
This book will guide financial institutions in developing new approaches and solutions for handling perennial issues. Emphasizing the value of creativity for project management in the banking sector, the author provides new insights for all those working in banking and finance. Presenting a number of new, outside-the-box ideas, the book can be regarded as the missing spice that will creatively transform all other ingredients in the monetary world.